Modification of Intestinal Microbiota Dysbiosis by Low-Dose Interleukin-2 in Dermatomyositis: A Post Hoc Analysis From a Clinical Trial Study - Zhufeng, Yunzhi; Xu, Jun; Miao, Miao; Wang, Yifan; Li, Yimin; Huang, Bo; Guo, Yixue; Tian, Jiayi; Sun, Xiaolin; Li, Jing; Lu, Dan; Li, Zhanguo; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
The microbiota has been observed altered in autoimmune diseases, including idiopathic inflammatory myopathies (IIMs), and associated with different treatments. Low-dose IL-2 treatment emerges as a new option for active IIMs. This study aims to explore the role of low-dose IL-2 in regulating intestinal dysbiosis involved in the IIMs. In this study, 13 patients with active IIMs were enrolled and received 1 ×106 IU of IL-2 subcutaneously every other day for 12 weeks plus standard care. The clinical response and immune response were assessed. Stool samples were obtained to explore the structural and functional alterations of the fecal microbiota targeting the V3–V4 region of the 16S rRNA gene and analyze their associations with clinical and immunological characteristics. Our study demonstrated that gut microbiota decreased remarkably in patients with IIMs, compared to healthy controls. The inflammatory-related bacteria, such as Prevotellaceae increased, while some butyrate-producing bacteria, such as Pseudobutyrivibrio, Lachnospiraceae, Roseburia, and Blautia, decreased significantly. The alteration associated with disease activities in patients with IIMs. After low-dose IL-2 treatment, 92.31% (12/13) of patients achieved IMACS DOI at week 12. Proportion of Treg cells significantly increased at week 12 compared with that in baseline (15.9% [7.73, 19.4%] vs. 9.89% [6.02, 11.8%], P = 0.015). Interestingly, certain butyrate-producing bacteria increase significantly after IL-2 treatment, like Lachnospiraceae, Pseudobutyrivibrio, etc., and are associated with a rise in L-Asparagine and L-Leucine. The effects of low-dose IL-2 on gut microbiota were more apparent in NOD mice. Together, the data presented demonstrated that low-dose IL-2 was effective in active IIMs and highlighted the potential for modifying the intestinal microbiomes of dysbiosis to treat IIMs.